Implementation and Legitimization of the Results of Remote Electronic Voting in the Regions of Russia: Features of Urban and Rural Practices - Anton G. Arutynov (RUDN Journal of Political Science, 2023)
Remote electronic voting (REV) as technology is gradually taking root in the political practice in Russia. As the technology is legally and chronologically new, it is both interesting and necessary to explain its implementation, as well as to identify the technological basis of the REV and, therefore, questions about the potential illegal use of this technology. This study aims at identifying the elements of the analysis of the implementation and legitimation of REV in cities and villages across Russia. The research is based on qualitative sociological and general logical methods: in general, the author uses the dialectical-materialistic approach, as well as the tools of comparative politics. A series of expert interviews were conducted in 10 regions of Russia. The results of the study showed that the Central Election Commission of the Russian Federation, the regional election commissions of the subjects of the Russian Federation, as well as regional and municipal authorities where the REV is being held, are at this stage looking for specific technologies to legitimize electronic voting. These practices will differ not only when comparing different regions, but also, most often, within one subject. One of the most significant differences will be noticeable with the introduction of REV in highly urbanized massifs and rural areas. Urban areas are characterized by the wide usage of political technologies to attract voters to electronic voting and legitimize it. Significantly larger budgets are invested in propaganda materials, including large, printed products (billboards, advertising at bus stops, and public transport). The idea of electronic voting is being promoted in social networks, mainly through VK, Telegram, Odnoklassniki, and WhatsApp. The rural areas, meanwhile, are characterized by activities aimed at personal contact with the voters and the use of informal connections. At the same time, today messages in social networks also reach rural residents, although most often it is not a purposeful activity, but a background capture of the audience. Concerning the improvement of the technological basis and the expansion of the geography of the REV, we can further elaborate on its legitimization and implementation, including in the context of the issues identified in this study.